PARTICULAR CHARACTERISTICS OF BABBIT B83, PRODUCED BY TURBULENT WAY OF CASTING - B. A. Potehin; V. V. Ilushin; A. M. Hristolubov (Литьë и металлургия, 2010)
It is shown that the new turbulent way of casting of slip bearings not only removes liquating heterogeneities and qualitatively improves morphology of intermetallides in babbit B83, but also extends the possibilities of its application.